When Can You Think Something? - Laursen, John Christian (Daimon Revista Internacional de Filosofia, 2013)
A review essay on what some scholars have said about heterodox thinking in Spain in the eighteenth century, contrasted with evidence from the reviewed book, which is on the Galician inquisition.